Bibliometric Profile of Turkish Journal of Psychology - Umut Al; Recai Çoştur (Türk Kütüphaneciliği)
The Turkish Journal of Psychology has been indexed by the Social Science Citation Index since 1995. This study examines the Turkish Journal of Psychology and bibliometric features of its articles.  The research carried out covers 118 articles between the years 1995-2005.  The following research ques- tions have been addressed: 1) What are the subjects of the articles? 2) Is multi- ple authorship a prevalent feature of the articles? 3) What are the institutional affiliations of the authors of the articles? 4) What are the common characteris- tics of the cited articles? 5) Which types of sources (journal articles, mono- graphs, etc.) get cited more often in the articles? 6) What are the most frequent- ly cited journals in the TJP? 7) Does the distribution of citations to journals fit Bradford's Law of Scattering? 8) Is there a relationship between the impact fac- tors of journals and the number of citations they get? 9) What is the rate of lit- erature obsolescence in psychology? 10) With regard to impact factor, what is the position of the TJP? Almost all of the articles were written in Turkish. The important part of the contributors was affiliated with Hacettepe, Ankara and the Middle East Technical universities. This research showed that 57% of articles (67 articles) published in Turkish Journal of Psychology received no citations remaining 43% (51 articles) were cited 135 times. The author self-citation ratio was 34%. In addition, journal self-citation ratio was 41%. Journals received 69% of all cita- tions in the Turkish Journal of Psychology. Journal of Personality and Social Psychology, Turkish Journal of Psychology, Child Development, Developmental Psychology and Psychological Bulletin were among the most frequently cited journals. Articles that appeared in the top 18 journals received 33% of all citations. The half-life of sources cited in the Turkish Journal of Psychology was ten years. According to the impact factor rank, the Turkish Journal of Psychology has been at the bottom of psychology journals which indexed by the Social Science Citation Index.